A Light from Within: Aesthetic Judgments and Emotional Responses to Viewing Religious Stained-Glass Windows - Mason, Elizabeth Ann (Trinity College Dublin. School of Psychology. Discipline of Psychology, 2024)
Aesthetic psychology is the study of aesthetic objects and scenes in our world and how different factors of our experiences - be they personal to the individual observer or facets of the aesthetic object or scene itself - influence our responses and judgments. Such objects include landscapes, paintings, architecture, and even consumer products. One as-yet unexplored medium of aesthetic research is stained-glass windows, which present the unique opportunity to explore how artificial and natural aesthetic experiences interact to create one entire experience. The purpose of the present thesis is to introduce the potential of this research focus by examining how individual differences - namely, expertise and religiosity - and feature-specific factors - namely, visual complexity and light variation - influence aesthetic judgments. In Experiment 1, we examine how experts differ from non-experts in their evaluations and emotional and physiological responses to stained-glass windows. In Experiment 2, we explore the influence of light variation on aesthetic judgments and preferences in religious and non-religious individuals. The findings from both investigations indicate the impact of bottom-up factors on aesthetic evaluations and emotional responses, while the influences of individual factors require further exploration. By shedding light on these interactions, our research serves as an initial step forward into exploring the potential of stained-glass in aesthetic research as a unique combination of aesthetic features.
APPROVED
Keywords: Aesthetic Perception; Individual Differences; Awe; Pupillometry; Stained-Glass Windows; Expertise; Religiosity